Controlled Synthesis of Ultrathin Sb2Se3 Nanowires and Application for Flexible Photodetectors. Issue 10 (25th June 2015) - Chen, Guihuan; Wang, Wenliang; Wang, Chunde; Ding, Tao; Yang, Qing
<x xml:space="preserve">Abstract</x> A new solvothermal approach is introduced to synthesize ultrathin Sb2Se3 nanowires with diameters ranging from 10 to 20 nm and with length up to 30 μm. The Sb2Se3 nanowire‐based photodetectors are firstly fabricated on polyethylene terephthalate and printing paper substrates, which exhibit excellent response to visible light with fast response time (0.18 and 0.22 s), high flexibility, and durability.